The epic quest for agile teamwork discovering the hidden power of spiritual intelligence - Kenan Fernando; Lieli Suharti (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
Agile teamwork has become increasingly important in higher education as faculty members are expected to collaborate across academic, administrative, and institutional responsibilities. However, the non-technical and relational mechanisms that support agile teamwork quality among lecturers remain insufficiently explained, particularly in relation to spiritual intelligence. Previous studies have mostly examined spiritual intelligence as an individual-level attribute, while limited empirical attention has been given to how it may contribute to team-level agility through specific teamwork mechanisms. This study examines the relationship between spiritual intelligence and agile teamwork quality through the mediating roles of cooperative goal interdependence, teamwork values, and mutual accountability. A quantitative explanatory design was employed using survey data from 272 lecturers working at private universities with excellent accreditation in Central Java, Indonesia. Respondents had prior teamwork experience and at least five years of work experience. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that spiritual intelligence is positively associated with cooperative goal interdependence, teamwork values, and mutual accountability. These three mediators are also positively related to agile teamwork quality, with mutual accountability showing the strongest direct effect on agile teamwork quality and the strongest mediating effect in the model. These results suggest that spiritual intelligence supports agile teamwork not only through shared goals and values, but especially through the development of collective responsibility among faculty members. The study contributes to the literature by extending spiritual intelligence into the context of faculty teamwork and by identifying mutual accountability as a central mechanism in strengthening agile teamwork quality in higher education.